Primary Mature Cystic Teratoma Compressing the Prostate in a 28-Year-Old Male: A Case Report and Literature Review - Khalil Chalhoub; Rawad Abou Zahr; Elias Mansour; Mona Aoun; Michel Jabbour (Case Reports in Urology)
Primary mature retroperitoneal teratomas are rare tumors most commonly occurring in adult females. These tumors are usually asymptomatic since they have no attachments to specific organs. We present a rare case of a 28-year-old male with 2-month history of lower urinary tract symptoms, who was found to have a primary mature cystic teratoma abutting the prostate.